(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO - 1. Il crocifisso in classe davanti alle Sezioni Unite - 2. Laicità dello Stato e autonomia scolastica - 3. Conflitto tra diritti e reasonable accommodation - 4. La regola della reasonable accommodation nella giurisprudenza straniera e italiana - 5. Il crocifisso come simbolo “essenzialmente passivo” nella giurisprudenza europea - 6. Reasonable accommodation in assenza di una lesione di diritti: rilievi critici - 7. Bilanciamento dei diritti e legislazione scolastica - 8. Il rapporto asimmetrico tra docente e alunni nella scuola: un dato del tutto omesso - 9. La rimozione del crocifisso da parte del docente: un atto lecito? Osservazioni conclusive. The Supreme Court’s United Sections on the Crucifix controversy in schools: searching for a difficult balance between laicism and European case-law ABSTRACT: This paper examines critically, in the light of the Italian and European case-law, the contents and the juridical arguments of a recent decision issued by the United Sections of the Italian Court of Cassation concerning the Crucifix controversy arisen in a State school. The judges established, on one hand, that the crucifix may be hung in a classroom upon demand of the students as it does not infringe the dissenting teacher’s freedom of conscience or of teaching, according to Lautsi ECHR decision (2011); on the other hand, the clash of values involved would need a reasonable accommodation which could require other religious symbols alongside the crucifix or its removal during the lessons of the dissenting teacher. Such a decision, according to the author, appears to be somewhat contradictory and ambiguous, and it does not resolve the case in a well-balanced way.